Study the effect of changing positions on some of the spectral properties of the new Azo dye [sodium (E)-7-amino-3-((2-(hydrogenarsonato) phenyl) diazenyl)-3-hydroxynaphthalene -1-sulfonate] and compare it with other Azo dye prepared in advance [sodium (Z)-4-amino-2-((2-(hydrogenarsonato) phenyl) diazenyl)-4-hydroxynaphthalene -2-sulfonate] - ثامر أعبيد, هادي (University of Thi-Qar Journal of Science, 2017)
This study included preparation of a new azo dye (D1) derived from Ortho-arsanilic acid 1-amino-2-naphthol-4-sulphonic acid using diazotization and coupling method. The fourier transform infrared spectroscopy (FT-IR) technique, ultraviolet–visible spectroscopy and CHN elemental analysis were used to identified and study the spectroscopic properties for a new azo dye. The obtained results were compared with previous results for another Azo dye (D2) by using same techniques above. Moreover, the pH effect on absorption spectra was studied by using various buffer solutions (different pH) in the visible region range between 350 nm to 600 nm. In addition, this study was involved calculation of the ionization and protonation constants using the half height method. Furthermore, this research paper investigated the effect of different polar organic solvents on visible absorption, absorption peaks (λmax) and absorption coefficient Molars (ε max).